Economic Analysis of Cassava Value Chain Products in Etche Local Government Area, Rivers State, Nigeria - Okuduwor A. A; Worlu A. A; Oyibo S. J (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research work on the economic analysis of cassava value chains was conducted in Etche LGA, Rivers State. The objectives of the study were to analyze the socio-economic characteristics of the respondents, examine the economic impact of cassava value-chain products, evaluate the profitability of cassava value-chain products, and identify constraints faced in cassava conversion. The findings also showed that inadequate finance, poor road network, high cost of cassava tubers, high cost of transportation, inadequate processing materials, poor package facilities, low income of farmers, sourcing of labor, and lack of or inadequate storage facilities were major constraints to the conversion of cassava to fufu, garri, starch, and flour. The study concluded that the cassava value chain is lucrative and highly profitable in the study area. It was recommended that funds be provided for them to acquire more lands and processing materials for maximum production, and individual and communal efforts should be harnessed to provide efficient processing and storage facilities where processors can assess at very affordable prices for the general public.